Improved energy recovery from food waste through hydrothermal carbonization and anaerobic digestion. (1st April 2022) - Mannarino, Gemma; Sarrion, Andres; Diaz, Elena; Gori, Riccardo; De la Rubia, M. Angeles; Mohedano, Angel F.
Graphical abstract: Highlights: Food waste was valorized by hydrothermal carbonization and anaerobic digestion. The combustion properties of hydrochar complied with ISO/TS 17225–8. Methane yield of process water reached values up to 154 mL CH4 STP g −1 CODadded . Anaerobic digestion promoted the removal of specific recalcitrant compounds. Good energy recovery yield can be obtained from combustion of hydrochar and methane. Abstract: Here we studied energy valorization of food waste by hydrothermal carbonization coupled with anaerobic digestion. Hydrothermal treatment was carried out at 200 °C and 230 °C for 1 h, obtaining hydrochar with properties suitable for solid biofuel according to ISO/TS 17225–8. The increase in temperature improved the fuel properties of hydrochar (higher heating value 20.3 and 23.7 MJ kg −1, fuel ratio 0.33 and 0.37, energy density 1.07 and 1.25). The anaerobic digestion of process water achieved methane yields around 150 mL CH4 STP g −1 CODadded and made it possible to remove some specific recalcitrant compounds, such as 2-methylpyridine and 2-ethyl-3-methylpyrazine. Energy recovery from hydrochar and process water seems to be an interesting alternative way to sustain the process energetically and economically, despite the significant energy inputs required for hydrothermal carbonization.